Plant Molecular Biology An International Journal on Molecular Biology, Molecular Genetics and Biochemistry - Seki, Motoaki; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Plant Molecular Biology is an international journal dedicated to rapid publication of original research articles in all areas of plant biology.The Editorial Board welcomes full-length manuscripts that address important biological problems of broad interest, including research in comparative genomics, functional genomics, proteomics, bioinformatics, computational biology, biochemical and regulatory networks, and biotechnology. Because space in the journal is limited, however, preference is given to publication of results that provide significant new insights into biological problems and that advance the understanding of structure, function, mechanisms, or regulation. Authors must ensure that results are of high quality and that manuscripts are written for a broad plant science audience. Plant Molecular Biology receives many gene discovery and/or gene sequence papers. While the Editorial Board encourages papers in plant functional genomics, computational approaches, and bioinformatics, we have made it a policy that gene discovery papers must be accompanied by significant new biological, biochemical or protein structural information. The Plant Molecular Biology Editorial Board discourages submission of manuscripts that do not follow this editorial policy. Manuscripts reporting the cloning of new genes without functional information obtained from biochemical assays, genetic analysis, or other appropriate experimental approaches will not be considered and returned without review. Reports on genes whose function has already been analyzed in other plant systems will be considered only if the research significantly advances our understanding of their biological function and regulation. Supporting results from DNA, RNA and protein blots, or limited in situ analysis experiments, are not sufficient documentation for gene function or regulation. Manuscripts reporting new experimental techniques, construction of DNA libraries, mutant collections, phylogenetic analysis, or computational methods will be considered only if they provide important new information or significant resources to the plant community. As a service to authors, Plant Molecular Biology offers: Free color submissions; Speed of publication: immediate posting of accepted paper on the Springer web; Listed in the top ranking of the ISI listing; Rapid and top-quality reviews; Mini-reviews on important topics; Special attention to high quality illustrations; No page charges; Free notification service on new publications via Springer Online; Online availability for institutions. .
Keywords: Biochemistry; Plant science; Botany; Plant pathology; Plant Sciences; Biochemistry, general; Plant Pathology